THE MODERN PROBLEMS OF FAITH AND REASON IN PHILOSOPHY: AUGUSTINE’S EMPHASIS - Parida, Alakananda (ShodhKosh: Journal of Visual and Performing Arts, 2023)
If there is a God, it’s possible that He cannot be fully understood through human reason alone. If reason could grasp religious truths, faith wouldn’t be necessary. The need for faith suggests that reason has limitations. But why is that the case? It could be because the human mind is incapable of fully understanding God's mysteries, meaning that certain religious truths (like the Resurrection or the Day of Judgment) are beyond the reach of unaided reason. Alternatively, these truths may not be provable and can only be shown to be plausible or possible. Or perhaps our minds are impaired and need to be trained, either through faith, virtue, or both, to reason more effectively and not simply rationalize. Let us delve further into the modern problem of Faith versus Reason in philosophy.